ASPECTS REGARDING THE CORRELATION OF THE NUMBER OF SERIES/PARALLEL-CONNECTED PHOTOVOLTAIC MODULES WITH THE INVERTER INPUTS - Alina Tatiana NEAMT; Liviun NEAMT; Olivian CHIVER; Eleonora POP; Mirela ILIA; Ciprian BUD (Carpathian Journal of Electrical Engineering)
Because the photovoltaic system performance is significantly influenced by the environmental factors, particularly temperature and irradiance, a right correlation between the number of series/parallel-connected photovoltaic modules with the inverter inputs must be achieved to guarantee the safety of all components and the system in its entirety, and a high efficiency in electrical energy production. This paper addresses these issues and presents the results in a very simple and illustrative manner very easily to be implemented in the design procedure of a photovoltaic system.